การศึกษาบทบาทของผู้บริหารในการโค้ชเพื่อพัฒนาครูบนฐานเทคโนโลยีการจัดการเรียนรู้ในโรงเรียน - แต้วัฒนา, ธนรัตน์; พูลสุวรรณ, ศิริยุภา; ธีรสวัสดิ์, ภัทธิรา; อินทรัศมี, พัชนา (Journal of Research and Curriculum Development, 2021)
The purpose of this study was to study how to coaching of the school administrators’ roles to teacher development based on technology for learning management in school. The research study consisted of five stages: 1) set guidelines for the develop a digital mindset of the school administrators through online training, 2) define content and knowledge to develop the school administrators to become coaches, 3) organize an online training process, 4) analyze content of the coaching process worksheet and 5) submit a synthesis report to the school administrators. The population was the school administrators participating in CONNEXT ED Foundation project 1,067 schools and the sample groups were school administrators who acted as coaches for 357 administrators. The research findings showed that the school administrators have digital thinking and knowledge of educational technology, able to apply the knowledge in coaching plan using learning management technology in areas including: analyze the situation of the teacher, coaching topic, coaching objectives, coaching goals, coaching activities and follow-up of coaching. All of these have a clear direction of development and coaching approach consists of 4 steps: 1) analysis 2) create the plan 3) follow up and feedback and 4) communication. While coaching process was extrinsic motives that was an external drive that encourages teachers to develop behaviors that can affect permanent change. If school administrators continue to stimulate the use of technology in learning management for teachers.